AGRI (AGua para RIego) - Valencia Gómez, Jefferson; Monserrate Rojas, Fredy Alexander; Quintero, Marcela (2019)
AGRI-Honduras Online is a Web GIS Application to identify potential sites for supplying water to communities for potable water and smallholder irrigation uses